Employee performance review of servant leadership and organizational commitment at the Samaya Seminyak Bali Hotel - I Ketut Sirna; Ni Putu Budihari Saputri; I Nyoman Tingkes (President University, 2022)
This study aims to determine partially and simultaneously servant leadership and organizational commitment to employee performance at The Samaya Seminyak Bali. Proportional Random Sampling method, the number of samples is 51 employees. Data analysis using Validity Test, Reliability Test, Partial Correlation Analysis, Multiple Correlation Analysis, Multiple Linear Regression Analysis, Coefficient of Determination Test, the research shows that (1) servant leadership has a positive and significant effect on employee performance, with the results of regression analysis of X1 = 0.295, (2) organizational commitment has a positive and significant effect on employee performance, with the results of regression analysis of X2 = 0.593, (3) simultaneously servant leadership and organizational commitment have a positive and significant effect on employee performance, obtained multiple linear regression analysis of Y = 12.251+0.295X1+0.593X2, and the coefficient of determination shows 21.3%. Based on these results, it can be concluded that servant leadership and organizational commitment are very influential partially and simultaneously on employee performance at The Samaya Seminyak Bali.